Surgical Bailout Therapy after Implantation of a Medtronic CoreValve Bioprosthesis - Rita Calé; José Neves; Rui Teles; João Brito; Miguel Abecasis; Manuel Almeida; Tiago Nolasco; Miguel Mendes (Case Reports in Cardiology)
Moderate-to-severe paraprosthesic leak causing hemodynamic deterioration and left ventricular remodeling can occur after transcatheter aortic valve implantation (TAVI). We present the case of a 75-year-old woman who underwent TAVI with a 26 mm CoreValve prosthesis complicated with an acute left ventricle dilatation due to a severe paravalvular leak. Patient was unresponsive to elective balloon post-dilatation, and therefore she was successfully treated with open-heart surgery to remove the malfunctioning CoreValve bioprosthesis and perform standard aortic valve replacement.